Estimating the economic consequences of an increased medication adherence due to a potential improvement in the inhaler technique with Spiromax® compared with Turbuhaler® in patients with moderate-to-severe chronic obstructive pulmonary disease in Spain - Darbà J; Ramírez G; García-Rivero JL; Mayoralas S; Pascual JF; Vargas D; Bijedic A (Dove Medical Press, 2017)
Josep Darbà,1 Gabriela Ramírez,2 Juan L García-Rivero,3 Sagrario Mayoralas,4 José Francisco Pascual,5 Diego Vargas,6 Adi Bijedic7 1Department of Economics, Universitat de Barcelona, 2BCN Health Economics & Outcomes Research S.L., Barcelona, 3Hospital Laredo, Cantabria, 4Hospital Ramón y Cajal, Madrid, 5Hospital General Universitario de Alicante, Alicante, 6Hospital de Alta Resolución el Toyo, Andalusia, 7Market Access and HEOR Department, TEVA Pharmaceutical, Madrid, Spain Objective: The objective of this study was to estimate the economic impact of the introduction of DuoResp® Spiromax®, budesonide/formoterol fixed-dose combination (FDC), focusing on an increase in medication adherence due to an enhancement of the inhalation technique for the treatment of COPD patients in Spain and 5 regions including Andalusia, Catalonia, Galicia, Madrid, and Valencia.Methods: A 4-year budget impact model was developed for the time period of 2015–2018. This study aimed at evaluating the budget impact associated with the introduction of DuoResp Spiromax in comparison with Symbicort® Turbuhaler® and Rilast® Turbuhaler. National and regional data on COPD prevalence were obtained from the literature. Input data on health care resource utilization were obtained by clinical consultation. Resource included primary care visits, specialist visits, hospitalization, and emergency room visits as well as the length of hospital stay. Based on both pharmacological and health care resource costs, overall annual treatment cost per patient was estimated in EUR 2015. Results: It was calculated that 130,777 adults were treated with budesonide/formoterol FDC delivered by a dry powder inhaler, Turbuhaler, in Spain in 2015. However, the target population decreases over the next 4 years. This pattern was observed in 4 regions, but for Andalusia, the treated population increased slightly. The overall budget savings in Spain with the market share of DuoResp Spiromax were estimated to be €6.01 million for the time period of 2015–2018. Region-specific data resulted in savings of €902,133 in Andalusia, €740,520 in Catalonia, €464,281 in Galicia, €748,996 in Madrid, and €495,812 in Valencia for the time period of 2015–2018. Conclusion: The introduction of budesonide/formoterol FDC delivered by Spiromax for COPD treatment is likely to contribute in a reduction of health care costs for Spain and in 5 Spanish regions. This model forecasts that Spain and these 5 Spanish regions were likely to have savings, which might be due to fewer days of hospitalization, avoided emergency room, and primary care visits. Keywords: dry powder inhaler, economic evaluation, region-specific estimates, payers’ perspective